Preparation of chitosan-TiO2 composite film with efficient antimicrobial activities under visible light for food packaging applications. (1st August 2017) - Zhang, Xiaodong; Xiao, Gang; Wang, Yaoqiang; Zhao, Yan; Su, Haijia; Tan, Tianwei
Graphical abstract: Highlights: TiO2 nano-powder was uniformly dispersed into chitosan to form chitosan-TiO2 film. Chitosan-TiO2 film showed enhanced hydrophilicity and better mechanical properties. Chitosan-TiO2 film possessed efficient antimicrobial activity under visible light. Chitosan-TiO2 film provoked the leakage of cellular substances. Chitosan-TiO2 film extended their shelf life for packaging red grapes. Abstract: By incorporation of TiO2 nano-powder in chitosan, a chitosan-TiO2 composite film was prepared with efficient antimicrobial activity against food-borne pathogenic microbes and expected to be a promising food packaging material. Scanning electron microscopy analysis showed that the TiO2 nano-powder was successfully and uniformly dispersed into the chitosan matrix. TiO2 addition led to enhanced hydrophilicity, to better mechanical properties, and to decreased light transmittance in visible light region of the composite film. The chitosan-TiO2 film possessed efficient antimicrobial activity against four tested strains, i.e. Escherichia coli, Staphylococcus aureus, Candida albicans, and Aspergillus niger with 100% sterilization in 12 h. It moreover provoked the leakage of cellular substances through damaged membrane. The prepared chitosan-TiO2 film was tested for packaging red grapes to prevent microbial infection and extend their shelf life. Results were positive, stressing the potential of the novel bio-nano composite film for food packaging applications.